The Concept Of Justice In Maternal And Child Health Care Services - Sukendar; Bambang Sunaryo (International Journal of Law and Legal Ethics, 2025)
Despite improvements in maternal and child healthcare (MCH) outcomes in Indonesia, significant disparities persist, particularly in remote and underdeveloped areas. This study examines the concept of justice in MCH services, focusing on how justice is perceived and experienced by women in these regions. The study aims to explore how justice is applied in MCH services, focusing on equitable access, quality of care, and the inclusion of marginalized groups, particularly women from disadvantaged communities. A descriptive qualitative approach was used, relying on secondary legal materials, including academic journals, health policies, and regulations. Data were analyzed through content analysis to explore how justice principles, especially distributive justice, are reflected in MCH services. Findings show that justice in MCH services encompasses both equal access and preferential treatment for those in greater need. Rawls' Theory of Justice as Fairness provides a framework for understanding how policies should reduce healthcare inequalities and ensure equal opportunities for vulnerable populations. The study emphasizes the need for policies that prioritize the most disadvantaged groups, such as impoverished mothers and children, ensuring that justice in healthcare is both normative and actionable.